Skepticism and Virtue Epistemology: Wittgenstein and Sosa - Michael Willliams (Philosophies)
Ernest Sosa has long been a leading advocate of a virtue-theoretic approach to the traditional problems of epistemology. However, in a recent book his thoughts take a striking new turn. Appealing to our epistemic competencies, he argues, will not suffice to meet the skeptical challenge to our claim to have knowledge of the world around us. We must recognize that our epistemic competencies are exercised against a background of “proper default assumptions”: commitments concerning the world and our place in it that we cannot justify but can rely on without incurring epistemic fault. Sosa finds anticipations of this idea in Wittgenstein’s appeal to propositions “hinge” propositions which, though not known, “stand fast”. However, mere fast-standing beliefs, “unhinged from any broader virtue epistemology”, cannot explain how we come to have knowledge of a world whose character is independent of what we happen to think about it. I argue that the claim that our everyday knowledge of the world rests on a body of assumptions is a serious concession to skepticism, which Wittgenstein shows we need not make. Hinge propositions are not mere “standfast” beliefs: they are known with certainty. Wittgenstein offers a way of thinking about knowledge that Sosa does not consider. He also poses a challenge to commonly held views about how epistemology, to the extent that there is such a subject, should be pursued.